Journal of Geographical Sciences - Yao, Lu Feng.; Zheng, Du.; Zhao, Xin.; Yu, Xinfang; SpringerLink (Online service) (Heidelberg : Science Press : Imprint: Science Press, co-published with Springer.)
Co-sponsored by the Geographical Society of China and the Institute of Geographic Sciences and Natural Resources Research, CAS, Journal of Geographical Sciences aims to strengthen academic exchange on geography research between China and other countries, and to offer a forum for exchange between geographers in China and abroad. Journal of Geographical Sciences is a natural science journal, publishing articles related to physical process and spatial patterns at the earth's surface, physio-geographical elements and their interaction, global change and its regional response, characters and management of natural resources, landscape ecology and environmental construction, remote sensing, geographic information system and their applications in geographical research.
Keywords: Geographical information systems; Remote sensing; Physical geography; Nature conservation; Physical Geography; Nature Conservation; Geographical Information Systems/Cartography.; Remote Sensing/Photogrammetry.